A biologically driven model for rural wastewater management: feasibility and efficiency of algal-bacterial biofilm reactors for combined treatment and algae farming - Mathur, Megha; Choudhary, Poonam; Sujathan, Surya; Naaz, Farah; Trenado-Yuste, Carolina; Malik, Anushree (Frontiers in Water, 2024)
The study investigates the feasibility and performance of an indigenously designed algal-bacterial biofilm reactor (ABR) for treating graywater in rural areas. Focusing on both treatment efficacy and sustainability, the research explored two key areas: optimizing the ABR for efficient graywater treatment and evaluating the use of readily available, low-cost materials for its construction. To achieve this, ABR was optimized to handle the specific characteristics of rural graywater, including potential seasonal variations in nutrient concentrations. The optimized ABR’s adaptability was rigorously assessed across various operational modes—batch, fed-batch, and continuous—demonstrating consistent removal efficiencies for key pollutants (COD, nitrate-nitrogen, total dissolved phosphate, and total ammoniacal nitrogen) under changing conditions. The fiber support-based ABR demonstrated significant pollutant removal from rural graywater: 81% COD reduction, 49.5% nitrate-nitrogen (NO3-N), 88.46% total dissolved phosphate (TDP), and 83.42% total ammoniacal nitrogen (TAN) in batch mode. Moreover, there was almost complete removal of total suspended solids (from 142 mg L−1 on Day 1 to 0 mg L−1 on Day 6) and total coliform (39,000 CFU mL−1 to 30 CFU mL−1). Notably, these removal efficiencies remained consistent across fed-batch (and continuous operation modes), showcasing the ABR’s adaptability. This adaptability facilitated a significant increase in treatment capacity, scaling from 3 L treated in batch mode (6 days) to 40 L in fed-batch mode (12 days) and a continuous treatment rate of 20 L per day. Further enhancing the sustainability of this approach, the study successfully employed readily available natural materials like bamboo pipes and sheets for constructing the ABR. This innovative design resulted in a remarkable increase in biomass productivity (9.8 g m−2 day−1) compared to polypropylene fiber-based reactors (4.5 g m−2 day−1) with enhanced treatment potential for all the parameters in batch mode (77.7% COD removal, 86% NO3-N removal, 81% TDP removal, 92% TAN removal, and 100% removal of total coliforms). This is the first reported algae-bacterial biofilm system using bamboo for wastewater treatment, promoting local resource utilization and a bio-based sustainable approach for rural graywater treatment.